Dehydrogenation of propane over high silica *BEA type gallosilicate (Ga-Beta). Issue 22 (10th September 2019) - Nakai, Masahiro; Miyake, Koji; Inoue, Reina; Ono, Kaito; Al Jabri, Hasna; Hirota, Yuichiro; Uchida, Yoshiaki; Tanaka, Shunsuke; Miyamoto, Manabu; Oumi, Yasunori; Kong, Chang Yi; Nishiyama, Norikazu
Abstract : Propane was found to be dehydrogenated over the Brønsted acid sites derived from incorporated Ga in the 12-membered large micropores of a *BEA-type structure. Abstract : Propane dehydrogenation (PDH) is one of the most promising candidates for the propylene production process to meet the growing demand of propylene for the future. There is an urgent need to develop catalysts for PDH. In this work, we have synthesized high silica Ga-Beta as a new candidate for a catalyst from dealuminated zeolite using the dry gel conversion method. A high silica Ga-Beta catalyst with a Si/Ga ratio of up to 177 can be synthesized. In the PDH reaction, the synthesized Ga-Beta showed the highest propane conversion and the highest propylene yield amongst the Ga-based zeolites. The combination of the Ga species being incorporated into zeolite frameworks, its large microporosity and Brønsted acidity is likely to lead to the excellent catalytic performance of Ga-Beta. Moreover, Ga-Beta with a higher Si/Ga ratio shows a longer catalyst lifetime for the PDH reaction, since the coke deposition rate decreased with the decrease in the amount of acid. This work provides new insights for the PDH reaction over Ga-based zeolite catalysts, and contributes to the progress in the activation and transformation of light alkenes to value-added chemicals.